The old truck - Pumphrey, Jarrett; Pumphrey, Jerome (New York : Norton Young Readers, an imprint of W. W. Norton and Company, 2020)
"On a small family farm, an old truck falls into disrepair and lies nearly forgotten, except by the family's daughter. The truck is been part of her daydreams as she grows up and develops strength and independence. As an industrious young woman, she pulls the rusted and overgrown vehicle from its almost-grave and restores it"--
Ages 3-5.
Keywords: Trucks -- Fiction; Farm life -- Fiction; African Americans -- Fiction